A one-dimensional diffusive transport model to evaluate H2S generation in salt caverns hydrogen storage sites - Minougou, Jean Donald; Gholami, Raoof; Poirier, Simon (Gas Science and Engineering, 2024)
Salt caverns are considered a potential hydrogen storage site given the ductility, tightness, and chemical inertness of halite. In addition, unlike porous media, salt caverns require less cushion gas and allow more cycles of injection and production within a year. However, hydrogen is an electron donor for many hydrogenotrophic microorganisms including halophilic sulfate-reducing microbes (SRM) and hydrogen sulfide (H2S) can be generated in a cavern once sulfate and hydrogen become available in the aqueous phase. As salt deposits are often associated with large amounts of impurities such as anhydrite and gypsum, their dissolution during the leaching phase can release the required sulfate ions for SRMs to produce H2S once hydrogen diffuses and dissolves in the brine at the bottom of the cavern. In this study, a one-dimensional diffusive transport model was developed using PHREEQC to simulate sulfate reduction and H2S generation in a cavern at the gas-brine interface. The solution of Fick's diffusion equation was used to calculate the hydrogen concentration at each level of the 1D model while the kinetic rates of reactions were derived from reported experimental and field site observations of brine samples taken from salt caverns. The results obtained indicated that hydrogen consumption at the gas-brine interface can trigger H2S and methane formations. This is followed by a reduction in sulfate and carbonate concentration and a slight increase in pH due to the reduction of protons in the solution. It was also observed that the presence of Fe2+ ions can reduce the amount of the hydrogen sulfide production while Ca2+ ions slightly favour sulfate reduction due to the production of methane. Although the kinetic reaction rate of the reactions in the model is subject to a certain degree of uncertainty, the workflow and results this study can serve as a guide for the future storage of hydrogen in salt caverns. •A one-dimensional diffusive transport model was developed to evaluate sulfate reduction and H2S generation in a salt cavern.•Hydrogen consumption at the gas-brine interface can trigger H2S and methane formations.•Presence of Fe2+ ions in the brine can reduce the amount of the hydrogen sulfide production.•Presence of Ca2+ ions in the brine slightly favour sulfate reduction due to the production of methane.•The increase in pH by NaOH addition to the brine can reduce the H2S generation.